2021
DOI: 10.1039/d0nj05774f
|View full text |Cite
|
Sign up to set email alerts
|

SERS-based immunoassay using core–shell nanotags and magnetic separation for rapid and sensitive detection of cTnI

Abstract: Au-4MBA@Ag with a strong Raman signal was successfully synthesized, and combination with magnetic separation technology achieved sensitive detection of cTnI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…With this methodology, the increase in cTnI concentration increases the density of the signal probes on the surface of the magnetic beads, resulting in an enlargement of the SERS signal from the reporter molecule that allowed the biomarker quantification. Hu et al (2021) reported a proposal performing the immunoassay and the Raman measurements in the same container. The detection probes consisted of a monoclonal antibody-conjugated on gold-silver core-shell nanoparticles with 4MBA encapsulated between the two metals (cTnI-mAb-Au@4MBA@Ag).…”
Section: Label Free and Label Based Determination Of Ctni By Surface ...mentioning
confidence: 99%
See 1 more Smart Citation
“…With this methodology, the increase in cTnI concentration increases the density of the signal probes on the surface of the magnetic beads, resulting in an enlargement of the SERS signal from the reporter molecule that allowed the biomarker quantification. Hu et al (2021) reported a proposal performing the immunoassay and the Raman measurements in the same container. The detection probes consisted of a monoclonal antibody-conjugated on gold-silver core-shell nanoparticles with 4MBA encapsulated between the two metals (cTnI-mAb-Au@4MBA@Ag).…”
Section: Label Free and Label Based Determination Of Ctni By Surface ...mentioning
confidence: 99%
“… Schematic representation of different cTnI detection systems working in solution. (A) sandwich immunoassay, adapted from Hu et al (2021) and (B) 3D AuNPs-PEN substrate, adapted from Lee et al (2022) . …”
Section: Label Free and Label Based Determination Of Ctni By Surface ...mentioning
confidence: 99%
“…The proposed immunoassay demonstrated high specificity and sensitivity, being able to detect both H-FABP and cTnI in ultralow concentrations such as 0.6396 and 0.0044 ng/mL, respectively, hence promoting its implementation for an accurate diagnosis of AMI. Later on, based on the same principle, the group achieved a LOD of 9.8 pg/mL of cTnI, which is considerably lower than the approved cTnI threshold for the diagnosis of cardiac diseases, by using core-shell nanotags and a magnetic separation based SERS immunoassay by employing 4-mercaptobenzoic acid as an active Raman reporter, thus achieving a diagnostic tool with advantages such as specificity, ultrasensitivity, reduced costs of fabrication, ease-of-use, and no sample pre-treatment with promising reliability and stability [ 39 ].…”
Section: Surface Enhanced Raman Spectroscopy (Sers) Sensing Platformsmentioning
confidence: 99%
“…Table 1 summarizes a series of various biosensing technologies for cTnI that have been reported in recent years [31][32][33][34][35][36]. Compared with the existing and emerging biosensors, the packaged thin-walled microbubble biosensor has a lager measure range and lower DL of cTnI.…”
Section: Detection Of Ctnimentioning
confidence: 99%